Forgotten dead : mob violence against Mexicans in the United States, 1848-1928 - Carrigan, William D., 1970- (Oxford University Press, 2013)
Mob violence in the United States is usually associated with the southern lynch mobs who terrorized African Americans during the Jim Crow era. In Forgotten Dead, William D. Carrigan and Clive Webb uncover a comparatively neglected chapter in the story of American racial violence, the lynching of persons of Mexican origin or descent. Over eight decades lynch mobs murdered hundreds of Mexicans, mostly in the American Southwest. Racial prejudice, a lack of respect for local courts, and economic competition all fueled the actions of the mob. Sometimes ordinary citizens committed these acts because.